Mechanical and tribological properties of injection molded zirconia-alumina for orthopedic implants. Issue 21 (1st November 2022) - Terrizzi, Anna Rita; Fersini, Maurizio; Contaldi, Vincenzo; Kunjalukkal Padmanabhan, Sanosh; Einarsrud, Mari-Ann; Licciulli, Antonio
Abstract: Ceramics have gained great attention for hip and knee arthroplasty surgical procedures due to their ability to guarantee long-life performance in patients and are considered an alternative to existing metal systems. In the present study, zirconia toughened alumina (ZTA) for orthopaedic implants has been developed by Ceramic Injection Molding (CIM) process. Microstructural, mechanical and tribological studies have been carried out to establish whether the material is suitable for the purpose. The new CIM ZTA material obtained density up to 99.4%, toughness 6.1 MPa m 1/2, hardness 20 GPa, Young's modulus 320 GPa, and low coefficient of friction ranging between 0.08 and 0.13 under lubricated conditions, and between 0.11 and 0.34 in dry condition. To simulate the performance of the ZTA in vivo, i.e., the influence of material degradation on the ageing properties, accelerated hydrothermal aging was performed in vitro and good mechanical and tribological properties were confirmed for the developed ZTA.